Self-Regulated Learning Strategies for Enhancing Speaking Proficiency: A Case Study of English Education Students - Sri Sukma; Syarif Amin; Muflihun Muflihun (Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking proficiency is one of the most challenging skills for EFL students because it requires continuous practice and the ability to overcome linguistic and affective difficulties such as limited vocabulary, grammatical errors, pronunciation problems, and low confidence. Therefore, self-regulated learning plays an important role in helping students independently manage and improve their speaking development. However, limited studies have examined the use of self-regulated learning strategies as a continuous process across different phases of speaking development. This study aimed to identify the types of self-regulated learning strategies used by English Education students and explore how these strategies were independently applied in speaking development. This study used a qualitative case study design involving six sixth-semester students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that students developed their speaking proficiency through the phases of forethought, performance, and self-reflection by applying cognitive, metacognitive, motivational, social, and affective strategies. These strategies supported pronunciation, vocabulary, grammar, and fluency development through planning, speaking practice, monitoring, self-evaluation, peer feedback, and digital learning tools. The study concludes that self-regulated learning supports continuous speaking development in EFL contexts.